Determinants of Non-Performing Loans in Nepalese Commercial Bank: An Empirical Analysis - Pokhrel, Sushil; Dhungana, Bharat Ram; Poudel, Jharana; Sharma, Laxmi Kanta (Kshitiz Management Review, 2025)
Non-performing loans (NPLs) are a persistent challenge for Nepalese financial institutions, adversely affecting economic growth and financial stability. This study examines how bank-specific and macroeconomic variables relate to NPLs within Nepal's financial sector. NPLs refer to credit facilities overdue in payment of interest or principal. Analyzing data from ten Nepalese commercial banks (2014–2023), the research employs descriptive and causal-comparative methods. Key variables include return on assets (ROA), capital adequacy ratio (CAR), credit-deposit (CD) ratio, bank size, gross domestic product (GDP), and inflation. The results reveal that ROA, CAR, and bank size significantly influence NPLs, whereas the CD ratio shows a positive but insignificant correlation. GDP presents a negative yet insignificant relationship with NPLs, while inflation displays a significant negative correlation. The findings highlight the interplay between bank-specific metrics and broader economic conditions. Addressing NPLs requires targeted actions by bank managers and shareholders to optimize financial performance and safeguard Nepal's economic resilience.